Genomic and functional characterization of fecal sample strains of Proteus cibarius carrying two floR antibiotic resistance genes and a multiresistance plasmid-encoded cfr gene. (April 2020) - Zhu, Tingyuan; Liu, Suzhen; Ying, Yuanyuan; Xu, Lei; Liu, Yabo; Jin, Junjie; Ying, Jun; Lu, Junwan; Lin, Xi; Li, Kewei; Xu, Teng; Bao, Qiyu; et al.
Highlights: P. cibarius G11 carried two floR genes related with transposons, one encoded on the chromosome and the other on a plasmid. The cfr gene encoded on a plasmid named pG11-51, flanked by a pair of IS26s and with a resistance gene erm(C) near by. The mobile genetic elements played an important role in the resistance genes replication and the horizontal gene transfer. Abstract: The objective of this study was to investigate the molecular characteristics and horizontal transfer of florfenicol resistance gene-related sequences in Proteus strains isolated from animals. A total of six Proteus strains isolated from three farms between 2015 and 2016 were screened by polymerase chain reaction (PCR) for known florfenicol resistance genes. Proteus cibarius G11, isolated from the fecal material of a goose, was found to harbor both cfr and floR genes. Whole genome sequencing revealed that the strain harbored two copies of the floR gene: one was located on the chromosome and the other was located on a plasmid named pG11-152. Two floR -containing fragments 4028 bp in length were identical and showed transposon-like structures. The cfr gene was found on a plasmid named pG11-51 and flanked by a pair of IS 26 s. Thus, mobile genetic elements played an important role in floR replication and horizontal resistance gene transfer. Therefore, increasing attention should be paid to monitoring the spread of resistance genes and resistance in real time.